Efficacy of Certain Systemic Nematicides for the Control of Root-Knot Nematodes Under Glasshouse Conditions * - DABAJ, KHALIFA H.; KHAN, M. WAJID (The Libyan Journal of Agriculture, 2023)
The systemic nematicides Oxamyl-G (Vydate G), Oxamyl-L (Vydate L). Aldicarb (Temik). Fenamiphos (Nemacur). and Fensulfothion (Terracur) were tested at different dosages for the control of Meloidogyne javanica on tomato under glasshouse conditions. All nematicides except Vydate L. when applied at the time of inoculation, were effective in inhibiting the development of galls and eggmasses at all the dosages used. Nemacur was found to be the most effective since it completely inhibited development of galls and eggmasses. Oxamyl-G, Fensulfothion and Aldicarb were equally effective. However, at lower dosage rates there was little formation of galls and eggmasses. Oxamyl-L which was applied as foliar spray was not effective in controlling the disease. These nematicides, when applied two weeks following inoculation with the nematodes, were not effective.